2017
DOI: 10.11591/ijpeds.v8.i4.pp1903-1912
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Modelling for Permanent Magnet Synchronous Machine (PMSM)

Abstract: <span>It is important to predict the temperature in some of the essential parts in machine design to prevent the machine from any damage. Most researchers usually not given much attention on thermal analysis during machine design as much as the electromagnet design. Therefore, in this study, two types of thermal modelling were proposed to predict the temperature of a permanent magnet synchronous machine (PMSM). Infolytica ThermNet software has been used since the software is related to Infolytica Magnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results showed that the interior permanent magnet transverse flux motor cooling is very efficient due to the lack of end winding. Aziz and Atkinson [15] studied two types of thermal modeling methods to predict the temperature of a PMSM. The predicted temperature from the lumped parameter model and finite element analysis are compared, and the results were validated by experiment setup.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the interior permanent magnet transverse flux motor cooling is very efficient due to the lack of end winding. Aziz and Atkinson [15] studied two types of thermal modeling methods to predict the temperature of a PMSM. The predicted temperature from the lumped parameter model and finite element analysis are compared, and the results were validated by experiment setup.…”
Section: Introductionmentioning
confidence: 99%
“…In the design process, the model of PMSM [2], [3] along with its parameters is used instead of real motor. So to represent the parameters of the machine, mathematical model [2], [3], [10] is required. Similarly to find out the performance of PMSM, a non-linear mathematical model is applied but, the conventional linear techniques cannot be applied directly in this situation.…”
Section: Introductionmentioning
confidence: 99%
“…The input of ZSI has from the solar and fuel, and the supply of renewable energy are connected to the Z-source converter by using the switch. The inverter is connected to the motor for high speed and high efficiency of the system [13].…”
Section: Introductionmentioning
confidence: 99%